Significance of pulmonary resection in patients with metachronous pulmonary metastasis from pancreatic ductal adenocarcinoma: a retrospective cohort study - Mashiko, Taro (BMC Surg, 2021)
BACKGROUND: Pulmonary metastases from pancreatic ductal adenocarcinoma (PDAC) are relatively rare. Systemic chemotherapy is the first choice of treatment in patients with distant metastases, and the role of metastasectomy is controversial. The aim of the present study was to evaluate the outcome of patients with pulmonary metastases after resection of PDAC and the indications for metastasectomy. METHODS: We retrospectively analysed patients with pulmonary metastases as the first recurrence after resection of primary PDAC between January 2006 and December 2018. Clinical data were obtained from the patients’ medical records. Relapse-free survival (RFS) and overall survival (OS) were analysed using the Kaplan–Meier method, and statistical significance was evaluated by the log-rank test. RESULTS: Of the 417 patients with resected PDACs, 24 (7.9%) had pulmonary metastases. Six patients (25.0%) underwent pulmonary resection and 18 (75.0%) received systemic chemotherapy and best supportive care. There were no major complications requiring therapeutic intervention after pulmonary resection. The median RFS was 24.0 months (95% CI 10.8–37.2), and the 1-, 3-, and 5-year RFS rates were 66.7%, 33.3%, and 4.2%, respectively. The median OS was 50.0 months (95% CI 15.9–84.1), and the 1-, 3-, and 5-year OS rates were 95.8%, 70.3%, and 46.4%, respectively. All patients with resected pulmonary metastases were alive at the end of the study, whereas the median OS of the patients who did not undergo resection was 37.0 months (95% CI 34.4–39.6). Therefore, patients with resected pulmonary metastases had a significantly better prognosis (p = 0.008). CONCLUSIONS: Pulmonary resection may improve the prognosis in selected patients with pulmonary metastases from PDAC. However, the present study is based on a small number of patients and may include a selection bias; therefore, a multi-institutional prospective study is needed to clarify the indications for pulmonary resection.